Effect of rumen protected methionine and choline supplementation on leukogram profile, oxidative stress, inflammatory and immunomodulatory responses of Surti buffaloes during transition period - RATHWA, SAWAN D; CHAUDHARY, SANDHYA S; SINGH, VIRENDRA KUMAR; MANAT, TANVI D; PATEL, SANJAY B (The Indian Journal of Animal Sciences, 2023)
Present study was conducted to observe effect of supplementing rumen protected methionine and choline on leukogram profile, oxidative stress, inflammatory and immunomodulatory responses during transition period in Surti buffaloes. Twenty-seven pregnant Surti buffaloes were selected and divided into three groups of nine animals each with following diet regime: Group I (Control)-basal diet, Group II (RPM)-basal diet+rumen protected methionine and Group III (RPM+RPC)-basal diet+rumen protected methionine+rumen protected choline. Supplementation of RPM @ 10 g/buffalo/day and RPC @ 50 g/buffalo/day was done from -15 d prepartum to 30 d postpartum. Blood samples were collected at start of experiment, 1st, 3rd and 6th week postpartum. At 1st and 3rd week postpartum, significantly higher level of GSH, SOD as well as TAS and lower level of LPO were observed in Group II and III as compared to control. Group III had highest SOD as well as TAS and lowest LPO levels. TNF-α and haptaglobin during postpartum period were significantly lower in Group II and III. Group III had lowest levels of TNF-α at 1st and 3rd week and haptoglobin at 1st, 3rd and 6th week postpartum. In vitro neutrophil phagocytic activity and lymphocyte proliferation were significantly higher in Group III followed by Group II and control during entire postpartum period. It was concluded that supplementation of rumen protected methionine and choline during transition phase of Surti buffaloes reduces oxidative stress as well as inflammatory tendencies and increases antioxidant status as well as immune response. Beneficial effects of supplementing both are more than supplementing rumen protected methionine alone.